Oral rehabilitation with removable partial denture in a patient undergoing partial maxillectomy: a case report - Carlos Roberto Teixeira Rodrigues; Wesley Luis Rodrigues Pereira; Emanuelly Groetaers Silva; Julia Barboza da Silva; Ailton Sebastião Odorizi Júnior; Wander Rodrigues dos Reis; Gabriela de Souza Ovídio; Roberta Mansur Caetano (Faculdade São Leopoldo Mandic, 2024)
ABSTRACT The Removable Partial Denture stands as an effective rehabilitation choice for patients who have undergone partial maxillectomy surgery due to maxillary tumors, involving the partial surgical removal of the maxillary bone. Removable partial denture are meticulously designed to restore masticatory, phonetic, and aesthetic functions, thereby contributing significantly to enhancing self-esteem and aiding patients in resuming social activities. During the patient's history-taking phase, it is of paramount importance to assess the patient's overall health, psychological state, expectations, and limitations. Ensuring regular follow-ups is imperative to prevent complications and to guarantee the durability of the prosthesis. Prosthetic planning constitutes a critical phase and can pose challenges, especially in achieving proper retention, stability, and suitable supports. Factors such as the defect size, the number of remaining teeth, and the amount of remaining bone structures can influence the treatment prognosis. It is crucial to emphasize that lack of adequate planning can lead to rehabilitation failures, resulting in discomfort, compromised functionality, and even potential harm to the patient's health. In this context, this study aims to present a successful clinical case of a patient who underwent partial maxillectomy and was rehabilitated through a Removable Partial Denture fixed with clasps on the entire left upper hemi-arch. This case vividly illustrates the importance of a personalized approach to prosthetic rehabilitation in patients with partial maxillectomy, taking into account the specificities of each case and highlighting the necessity of interdisciplinary collaboration to achieve satisfactory outcomes.